(3fUGH GdGMJSGHs - (3YeQ Hf eMeO Hf YhV GdTGej GdMfaj GdSfGej,J (B696 (3g` s ((3MGLi eMeO GdTgjQ HGdfWb s)
(3ChdgG (B:s
(3GdMeO ddg GdMSjH GdQbjH Ydi fhGdg hHYO abO LeY YHOg ai JUfja gPG GdcJGH agh fUGH GdGMJSGH eSGFd GNJUJ HGdfSHI Edi MSH efUH GdMSHI s
(3BNQgG (B:s
(3hEPG GJJ GdeQCg GdbQjHI ddJYRjI aJfhM Ydi GdejJ gd jLhR ddeMJSH Cf jMRgG ef HjJ ZjQg GPG de jNQLgG Ggdg GdLhGH fYe dGf YeQ QVi GddY Yfg CNQL CNJ CHj HcQ QVi Gddg Yfg Mjf fGUMJ Ydjg ef UMjM GdHNGQi (B, s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B317s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs